A mixed-methods analysis of personal protective equipment used in Lassa fever treatment centres in Nigeria. Issue 3 (September 2021) - Holt, Andrew; Hornsey, Emilio; Seale, Anna C.; Rohan, Hana; Bausch, Daniel G.; Ihekweazu, Chikwe; Okwor, Tochi
Summary: Background: Lassa fever (LF) is a viral haemorrhagic fever endemic in West Africa. Lassa virus is maintained in and spread to humans from rodents, with occasional secondary human-to-human transmission. Present recommendations for personal protective equipment (PPE) for care of patients with LF generally follow those for filovirus diseases. However, the need for such high-level PPE for LF, which is thought to be considerably less transmissible between humans than filoviruses, is unclear. Aim: In Nigerian Lassa Treatment Centres (LTCs) we aimed to describe current PPE practices, identify barriers and facilitators to implementation of existing guidance, and assess healthcare workers' understanding. This would inform the development of future PPE guidelines for LF. Methods: We performed a mixed-methods study, including short cross-sectional surveys of PPE used in LTCs, observations of practice, and in-depth interviews with key informants. We described the quantitative data and we conducted a thematic analysis of qualitative data. Findings: Our survey of 74 HCWs found that approximately half reported problems with recommended PPE. In three LTCs PPE was used highly variably. Full PPE, as recommended in Nigeria CDC guidelines, was used in less than a quarter (21%) of interactions. In-depth interviews suggested this was based on availability and HCWs' own risk assessments. Conclusion: Without specific guidance on Lassa, the current approach is both resource and labour-intensive, where these are both limited. This has led to low adherence by health care workers, whose own experience indicates lower risk. The evidence-base to inform PPE required for LF must be improved to inform a more tailored approach.